Anomalous heat transfer for an open non-equilibrium gaseous system. (3rd May 2017) - Ilyin, Oleg
Abstract: The steady state of an open non-equilibrium one-dimensional system is considered using the linearized kinetic Bhatnagar–Gross–Krook (BGK) model. It is shown that the BGK model has a stationary distribution function describing a gas for which the heat flow and the temperature gradient has the same sign—heat is transferred from cold regions to hotter regions. This distribution function cannot be presented in the form of a truncated Grad expansion. A numerical study of a boundary problem with non-equilibrium special boundary conditions supports the theoretical predictions.